Apartment Ownership in Question: Legal Insights from Certificate-Based Cases in Rembang - Suryaningtyas, Asri (Indonesian Journal of Agrarian Law, 2024)
This study aims to analyze the legal aspects of apartment ownership in Rembang Regency, with a particular focus on the implementation of ownership certificates. The background of this research stems from the growing urgency to develop vertical housing in areas with limited land and the importance of legal certainty for unit owners. The research problems addressed include the legal framework governing apartment ownership, the types of ownership certificates applicable, legal challenges in their application in Rembang Regency, and possible legal solutions. This research employs a normative approach and a case study of available apartment ownership certificates. The analysis reveals that although the legal framework—particularly Law Number 20 of 2011 concerning Apartments—is sufficiently established, its local implementation still faces obstacles, especially regarding legal literacy and access to certified land. Therefore, active involvement of local government is needed to facilitate land certification, conduct legal education for the public, and strengthen implementing regulations at the local level.